Dengue fever in renal transplant patients: a systematic review of literature. Issue 1 (December 2017) - Weerakkody, Ranga; Patrick, Jean; Sheriff, Mohammed
Abstract Background Dengue fever in renal transplanted patients has not been studied well, and we review all the literature about episodes dengue fever in renal transplant patients. Methods The aim was to describe clinico-pathological characteristics, immunosuppressive protocols, need renal outcome and mortality. PubMed, LILACS, Google Scholar and Research Gate were searched for "Dengue" and "Renal/Kidney Transplantation" with no date limits. Hits were analyzed by two researchers separately. Results Fever, myalgia, arthralgia and headache was significantly lower than normal population, while pleural effusions and ascites were observed more. Incidence of severe dengue is significantly higher among transplant patients in this review, as well as they had a significantly higher mortality (8.9% vs 3.7%, p  = 0.031). Age, period after transplantation and immunosuppressive profile had no effect on disease severity, mortality or graft out come. Presence of new bleeding complications and ascites was associated with more severe disease (p  < 0.001 andp  = 0.005), death (p  = 0.033) or graft loss (p  = 0.035). Use of tacrolimus was associated with new bleeding complications (p  = 0.027), and with ascites (p  = 0.021), but not with thrombocytopenia. 25% of patients with primary disease fail to mount an IgG response by 15 weeks of the illness. 58.9% had graft dysfunction during illness. Postoperative transplanted patients were at risk of severe disease and unfavorable outcome. Conclusions The physical and laboratory findings in dengue fever in renal transplanted patients differ from the general population. Some degree of graft dysfunction is common during the illness, but only a minority develops graft failure.